Pole figure analysis from electron backscatter diffraction—an effective method of evaluating fiber-textured silicon thin films as seed layers for epitaxy. (25th January 2019) - Hainey, Mel; Robin, Yoann; Amano, Hiroshi; Usami, Noritaka
Abstract: Because of their >95% (111) surface orientation and very large (10–300  μ m) grain sizes, sub-50 nm Group IV thin films fabricated by metal-induced crystallization are promising seed layers for epitaxy. However, methods for evaluating Group IV film quality for subsequent homo-and heteroepitaxial growth have not been widely reported. Here, we show how pole figures obtained by electron backscatter diffraction allow for texture analysis and measurement of grain misorientation. Correlations with Group IV thin film processing parameters such as annealing temperature and film quality in heteroepitaxially grown GaN films are developed.